Effective Monitoring of Temperature and Humidity in Real-Time Wireless Sensor Method of Processor and System Architecture - Senthil, P. (Asian Journal of Science and Applied Technology, 2018)
Today, the place of the same word, “Analog Records” is in place for the work of WSN like it The system immune system for landing damage caused by analogue systems Storage in Memory. So it is that we have an excellent law completely automated Possible Accuracy More, such a comparison should be cheap as well as qualified transport. In this Paper introduces wireless sensor (WS) facts using communication software DHT11, Arduino Education At Bett 2017, SIM900A GSM module, sales tool and liquid crystal display (LCD). Heating system in experimental settings includes DHT11 transmission and use Ardino and SIM 900 GSM shield, Arduino, GSM shield, still in use displays a heating system for the LCD screen and thermal sensitive.